Designing Learning Evaluation Islamic Education - Dewita, Imel Putri; Markuna, Markuna (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This evaluation must be carried out continuously, comprehensively, and using various assessment instruments so that the data obtained is valid and reliable. Teachers, as the implementers of the evaluation, are required to have the ability to design appropriate instruments, process evaluation data, and apply objective, practical evaluation principles that involve students.Evaluation is an important activity carried out by educators in the learning process. With evaluation, educators can improve their competence in class management, both in choosing learning methods, media, teaching materials, and so on that can motivate students to learn. In addition, with evaluation, educators can find out the level of success of their students. Therefore, educators must carry out evaluation activities correctly. However, in reality, there are still many educators who have not carried out the evaluation process properly, especially in elementary schools. One of the causes is the lack of knowledge that educators have about the evaluation itself. So that knowledge is needed about the concept, role of evaluation and procedures for implementing evaluation in order to obtain evaluation results that can describe the actual condition of students.This article is compiled through a literature study method, which includes collecting information from various literature related to the topic of learning evaluation. The findings of this study underline that appropriate evaluation can support the achievement of learning objectives effectively, assist teachers in optimizing teaching strategies, and improve the quality of student learning outcomes.